Landsmann Solidarity among Turkish Citizens - (:unkn) unknown (ELSEVIER SCIENCE BV, 2015)
Compatriotship, favoring one's townspeople (Landsmann), is a special kind of nepotism prevailant in Turkish society. People from the same geographical region do come together and enjoy solidarity when they meet one another elsewhere. The idea of belonging carries strong burdens of responsibility along with it. The concept is of feudal nature and is loosening with modernization. Interestingly, compatriotship does not necessarily include favoring his own ethnicity. It also cuts throgh social classes, as well. (C) 2015 The Authors. Published by Elsevier Ltd.
Keywords: Compatriote; solidarity; feudal vestiges